2022
DOI: 10.20517/ss.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric and mechanical performances of ionic liquid-modulated PEDOT:PSS/SWCNT composites at high temperatures

Abstract: Significant progress has been achieved for flexible polymer thermoelectric (TE) composites in the recent decade due to their potential application in wearable devices and sensors. In sharp contrast with the booming TE studies at room temperature, the TE performances of polymer TE composites received relatively less attention despite the significance for the application of TE composites in the high temperature environments. The TE and mechanical performances of flexible poly (3,4 ethylenedioxythiophene):poly(st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The results reported here imply that enhancing the annealing temperature can increase the films elongation at break, possibly owing to the accelerated relaxation of polymer chains at elevated temperatures. 69,77 Meanwhile, temperature above a particular threshold causes deterioration or structural alterations that compromise mechanical stability. This degradation could include the breakdown of molecular bonds or the beginning of thermal decomposition, both of which result in a decrease in mechanical characteristics.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The results reported here imply that enhancing the annealing temperature can increase the films elongation at break, possibly owing to the accelerated relaxation of polymer chains at elevated temperatures. 69,77 Meanwhile, temperature above a particular threshold causes deterioration or structural alterations that compromise mechanical stability. This degradation could include the breakdown of molecular bonds or the beginning of thermal decomposition, both of which result in a decrease in mechanical characteristics.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The raw materials are all industrially available, and the fabrication route is based on a facile hot-pressing way without any solution, therefore exhibiting outstanding cost-effective and efficient fabrication features. Figure b,c compares the calculated ratios for S 2 σ/cost and S 2 σ/fabrication time between the as-fabricated EG 70 CF 27 PF 3 IL 6 film in this work and other conventional carbon-based thermoelectric materials including composites based on partial EG and carbon nanotubes (CNTs). Here, the S 2 σ/cost indicates the unit cost money ($) of the achieved peak S 2 σ (μW m –1 K –2 ), and the S 2 σ/time indicates the unit cost time for fabrication (min) of the achieved peak S 2 σ (μW m –1 K –2 ). The data of cost money are derived from the market research, while the data of cost time for fabrication are mainly derived from the reported literature. In this work, the S 2 σ/cost parameter of 148.8 μW g m –1 K –2 $ –1 and the S 2 σ/time parameter of 2.58 μW m –1 K –2 min –1 are both significantly competitive.…”
Section: Introductionmentioning
confidence: 99%
“…Figure b,c compares the calculated ratios for S 2 σ/cost and S 2 σ/fabrication time between the as-fabricated EG 70 CF 27 PF 3 IL 6 film in this work and other conventional carbon-based thermoelectric materials including composites based on partial EG and carbon nanotubes (CNTs). Here, the S 2 σ/cost indicates the unit cost money ($) of the achieved peak S 2 σ (μW m –1 K –2 ), and the S 2 σ/time indicates the unit cost time for fabrication (min) of the achieved peak S 2 σ (μW m –1 K –2 ). The data of cost money are derived from the market research, while the data of cost time for fabrication are mainly derived from the reported literature. In this work, the S 2 σ/cost parameter of 148.8 μW g m –1 K –2 $ –1 and the S 2 σ/time parameter of 2.58 μW m –1 K –2 min –1 are both significantly competitive. Besides, to evaluate the application potential of the as-designed composite films, a homemade thermoelectric device based on the performance-optimized films is designed (Figure d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides harvesting waste heat from factories, heat from photovoltaic cells [4] and high-power light-emitting diodes [5] have also shown potential for energy conversion through TE devices. On a smaller scale, a small temperature difference between the human body heat (waste heat energy) and the environment is also able to generate usable energy to power wearable electronic devices [6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%